Exploring the anticandida potentials of nanoparticles fabricated from tea leaf (Camellia sinensis) extracts: a systematic review - Naheem Adekilekun Tijani; Abdullateef Opeyemi Afolabi; Fred Mutanule; Sujithkumar Ganesh Moorthy; Danladi Makeri (Discover Materials)
Abstract Globally, large proportions of Candida species are becoming a major threat to human health as they are developing resistance to most available antifungal drugs. The recent adoption of nanoparticles as an intervening strategy against resistant microbes has proven efficient. Besides their antifungal activities, several studies have reported the anticandida properties of nanoparticles fabricated from plant materials. In this systematic review, available data from the literature on the anticandida potentials of nanoparticles biosynthesized from tea leaf (Camellia sinensis) extracts were compiled and analyzed. A total of 30 studies were generated from a literature search in three electronic databases i.e. Scopus, PubMed, and Embase, in accordance to the PRISMA guidelines. The retrieved studies were filtered based on inclusion and exclusion criteria. We included nine (9) eligible articles that highlighted the antifungal efficacy of nanoparticles mediated from tea leaf extract against Candida species. From the selected articles, the antifungal effect of synthesized NPs against C. albicans, C. tropicalis, C. glabrata, C. dubliniensis, and C. parapsilosis was reported and expressed by the zone of inhibition (ZOI) diameter and the minimum inhibitory concentration (MIC). The studies analysis showed the potency of plant extract-mediated NPs against Candida species, regardless of the heterogeneity of results that was spotted in the diameter of ZOI presented from one study to another.